Complete genome analysis of Tequatrovirus ufvareg1, a Tequatrovirus species inhibiting Escherichia coli O157:H7 - Maryoris Elisa Soto Lopez; Maryoris Elisa Soto Lopez; Marco Tulio Pardini Gontijo; Marco Tulio Pardini Gontijo; Rodrigo Rezende Cardoso; Laís Silva Batalha; Monique Renon Eller; Denise Mara Soares Bazzolli; Pedro Marcus Pereira Vidigal; Regina Célia Santos Mendonça (Frontiers in Cellular and Infection Microbiology, 2023)
IntroductionBacteriophages infecting human pathogens have been considered potential biocontrol agents, and studying their genetic content is essential to their safe use in the food industry. Tequatrovirus ufvareg1 is a bacteriophage named UFV-AREG1, isolated from cowshed wastewater and previously tested for its ability to inhibit Escherichia coli O157:H7.MethodsT. ufvareg1 was previously isolated using E. coli O157:H7 (ATCC 43895) as a bacterial host. The same strain was used for bacteriophage propagation and the one-step growth curve. The genome of the T. ufvareg1 was sequenced using 305 Illumina HiSeq, and the genome comparison was calculated by VIRIDIC and VIPTree.ResultsHere, we characterize its genome and compare it to other Tequatrovirus. T. ufvareg1 virions have an icosahedral head (114 x 86 nm) and a contracted tail (117 x 23 nm), with a latent period of 25 min, and an average burst size was 18 phage particles per infected E. coli cell. The genome of the bacteriophage T. ufvareg1 contains 268 coding DNA sequences (CDS) and ten tRNA genes distributed in both negative and positive strains. T. ufvareg1 genome also contains 40 promoters on its regulatory regions and two rho-independent terminators. T. ufvareg1 shares an average intergenomic similarity (VIRIDC) of 88.77% and an average genomic similarity score (VipTree) of 88.91% with eight four reference genomes for Tequatrovirus available in the NCBI RefSeq database. The pan-genomic analysis confirmed the high conservation of Tequatrovirus genomes. Among all CDS annotated in the T. ufvareg1 genome, there are 123 core genes, 38 softcore genes, 94 shell genes, and 13 cloud genes. None of 268 CDS was classified as being exclusive of T. ufvareg1.ConclusionThe results in this paper, combined with other previously published findings, indicate that T. ufvareg1 bacteriophage is a potential candidate for food protection against E. coli O157:H7 in foods.